Comparison of ablation index versus time‐guided radiofrequency energy dosing using normal and half‐normal saline irrigation in a porcine left ventricular model. (30th January 2022) - Larsen, Timothy; Du‐Fay‐de‐Lavallaz, Jeanne M.; Winterfield, Jeffrey R.; Ravi, Venkatesh; Rhodes, Paul; Wasserlauf, Jeremiah; Trohman, Richard G.; Sharma, Parikshit S.; Huang, Henry D.
Abstract: Background: Ablation Index (AI) is a multiparametric quality marker to assess the durability of radiofrequency (RF) lesions. The comparative effectiveness and safety of AI versus time‐based energy dosing for ablation of ventricular arrhythmias are unknown. Objective: We compared AI and time‐based RF dosing strategies in the left ventricles (LVs) of freshly harvested porcine hearts. Methods: Ablation was performed in vitro with an open‐irrigated ablation catheter (Thermocool ST/SF), 40 W, contact force 10–15 g. Tissue samples were stained in triphenyltetrazolium chloride for the measurement of lesion dimensions. Results: A total of 560 lesions were performed (AI‐group: [ n = 360]; time‐group: [ n = 200]). Using normal saline (NS) ( n = 280), growth in lesion depth slowed after 30 s and AI > 550 in comparison to width, volume, and magnitude of impedance drops which continued to increase with longer RF duration. Risk of steam pop (SP) was higher for RF > 30 s (RF < 30 s:1 SP [2.5%] vs. RF > 30 s: 15 SP [25%]; p = .002) or AI targets >550 (AI: 350–550: 2 SP [2%] vs. AI 600–750: 15 SP [19%]; p = .001). Using half‐normal saline (HNS) ( n = 280), lesion dimension and impedance drops were larger and growth in lesion depth slowed earlier (AI: 500). Risk of SPs was higher above AI 550 (AI: 350–550: 7 [7%] SPs vs. AI 600–750: 28 [35%] SPs; p < .00001). While codependent variables, correlation between AI and time was modest‐to‐strong but decreased with longer RF duration. Conclusion: In this ex vivo study, AI was a better predictor of lesion dimensions than ablation time and magnitude of impedance drop in the LV using NS and HNS irrigation. AI targets above 550 led to a higher risk of SPs. Future trials are required to verify these findings.